LINGUOCULTURAL ANALYSIS OF POLITINESS STRATEGIES IN ENGLISH AND UZBEK LITERATURE - Kurbanmuratova , Gulnaz (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article examines politeness strategies in English and Uzbek literary discourse from a linguocultural perspective. The analysis demonstrates that English literary tradition prioritizes the protection of individual autonomy through indirect speech and negative politeness strategies, while Uzbek literary tradition reflects a collectivist orientation in which hierarchical respect and communal solidarity predominate. Drawing on the works of Jane Austen, Harold Pinter, Alisher Navoi, and Abdulla Qodiriy, the study reveals that despite their cultural differences, both traditions employ indirectness as a primary politeness vehicle and use politeness conventions as instruments of social critique.